Intuitive Theories of Parenting and the Development of Emotion Understanding in Preschoolers - Daria Bukhalenkova; Margarita Gavrilova; Natalia Kartushina (MDPI AG, 2021)
Emotion understanding develops intensively in preschool and junior school. Although the parent/family environment has been shown to affect the development of emotion understanding in children, very little research has examined examined how parents' view upbringing and education and how they are related to their child's emotion understanding, given that the intuitive theories of parenting are reflected in actual parent behavior. This study fills this gap in the literature and examines the links between children's ability to understand emotions and their parents' intuitive theories of parenting. The sample was 171 5- to 6-year-old children and their parents. Analyses revealed a significant relation between intuitive theories of parenting and children's emotion understanding. In particular, the intuitive attitude of uninvolved parenting was associated with the understanding of mental causes of emotions and the overall level of emotion understanding in preschool children. Integrating these results will allow us to reach more informed conclusions about the role of parental beliefs in the development of emotion comprehension in preschool children.